1996
DOI: 10.1128/jvi.70.12.8368-8374.1996
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the human T-lymphotropic virus type 1 Tax dimer with CREB and the viral 21-base-pair repeat

Abstract: Human T-lymphotropic virus type 1 Tax interacts specifically with the cellular transcription factor CREB and the viral 21-bp repeat element to form a Tax-CREB-DNA ternary complex which mediates activation of viral mRNA transcription. Analyses of Tax and Tax mutants indicate that, like CREB, Tax incorporates into the ternary complex as a dimer. The ability of Tax to form a dimer is necessary for its interaction with CREB and the 21-bp element. Analyses of several Tax mutants with amino acid substitutions spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…It is noteworthy that for both proteins, Tax and CREB-2, the domains which have been reported to be involved in protein dimerization, the cysteine-rich and leucine-zipper subdomains, respectively, are necessary to form a stable complex. This observation suggests that dimerization of both proteins could be required for a specific interaction, as already suggested for Tax and CREB (39,76).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is noteworthy that for both proteins, Tax and CREB-2, the domains which have been reported to be involved in protein dimerization, the cysteine-rich and leucine-zipper subdomains, respectively, are necessary to form a stable complex. This observation suggests that dimerization of both proteins could be required for a specific interaction, as already suggested for Tax and CREB (39,76).…”
Section: Discussionsupporting
confidence: 72%
“…Tax-Tax dimer formation in yeast offers one simple explanation for these experimental results. Indeed, Tax functions optimally as a homodimer (76) and its cysteine-rich zinc finger domain is a necessary region for dimerization (39). In the case of the mutant Tax 308-353, the GAL4 DNA binding domain, which binds DNA as a dimer (16), is directly fused to the C-terminal domain of Tax and thus could compensate for the absence of the dimerization domain of Tax.…”
Section: Creb-2 Enhances Tax-mediated Transactivation In Vivomentioning
confidence: 99%
“…Tax acts potently through viral CREs on the LTR, which are also bound by CREB. For activation of HTLV-I LTR and cellular CREB-regulated genes, dimeric Tax forms a ternary complex with dimeric CREB and the viral CRE [54][55][56][57][58][59]. In one model for Tax activation of CREB, Tax is thought to potentiate the dimerization and DNA binding of CREB and other bZIP transcription factors [60][61][62].…”
Section: Requirement Of Creb For Viral Transformationmentioning
confidence: 99%
“…Paca- Uccaralertkun et al, 1994;Tang et al, 1998). In vitro, Tax contacts this G-C-rich DNA-flanking sequence and acts as an anchor to recruit the cellular coactivator CREB to the transcription complex (Kimzey and Dynan, 1998;Lenzmeier et al, 1998), which in turn functions as a dimer and interacts directly through its basic domain-leucine zipper with the CRE-like sequence to activate transcription from the viral LTR (Brauweiler et al, 1995;Goren et al, 1995;Laurance et al, 1997;Paca-Uccaralertkun et al, 1994;Tie et al, 1996;Yin and Gaynor, 1996;Giam 1991, 1992). Several studies have suggested that these interactions stimulate the dimerization of bZIP-containing proteins and their DNA-binding activity (Armstrong et al, 1993;Baranger et al, 1995;Perini et al, 1995;Tie et al, 1996;Wagner and Green, 1993;Yin and Gaynor, 1996).…”
Section: Seizing Of T-cells By Htlv-1mentioning
confidence: 99%